Characteristics of Credit Instruments Issued by Stokvels in South Africa - Ngcobo, Lindiwe; Chisasa, Joseph (Journal of Economics and Behavioral Studies, 2018)
Access to formal credit and other financial instruments remains a challenge for the majority of households in South Africa. The objective of this study was, therefore, to determine the characteristics of credit instruments issued by stokvels to households in South Africa. Prior studies have generally focused on mobilization of savings through stokvels while none has paid particular attention to the credit supply function of stokvels. This study attempts to fill this gap by using a self-administered research questionnaire on a sample of 386 respondents. Members of stokvels were surveyed from the cities of Pretoria and Johannesburg in the Gauteng province of South Africa. Data was analysed using descriptive statistics, exploratory factor and correlation analyses. Results show that stokvels issue short-term loans from less than 3 to 6 months. Interest rates are high ranging from 25% to 35% and are charged monthly. Loan sizes are small with approximately two-thirds of the respondents receiving loans above R500 while the remaining third received less than R500. Finally, all loans are secured by the borrower’s identification document or bank card and personal identification number. The results of this study have policy implications for financial institutions in South Africa.